221k views
0 votes
Simplify
(1)/(X-10) ÷
(9X)/(x^(2)- 9x -10)

1 Answer

5 votes

In the second fraction, factorize the denominator:


x^2-9x-10=(x-10)(x+1)

Then we have, as long as
x\\eq10,


\frac1{x-10}/(9x)/(x^2-9x-10)=\frac{\frac1{x-10}}{(9x)/((x-10)(x+1))}=\frac1{(9x)/(x+1)}=(x+1)/(9x)

which you could also write as


(x+1)/(9x)=\frac x{9x}+\frac1{9x}=\frac19+\frac1{9x}

User Made Baruna
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.